Building Digital Skills among Elementary Educators: A Training Program on Interactive E-Module Development - Nindy Profithasari; Siska Mega Diana; Erni Erni; Siti Nurjanah; Frida Destini; Niken Yuni Astiti; Agung Dian Putra; Hariyanto Hariyanto; Miranda Abung; Dian Permata Sari (Smart Society, 2025)
The rapid advancement of information technology demands a more dynamic and interactive learning environment, requiring educators to go beyond traditional teaching methods by integrating various digital tools to enhance student engagement and learning outcomes. However, limited digital proficiency among elementary school teachers poses a significant barrier to this integration. This study aimed to improve the digital competencies of elementary school educators through targeted training on the development of interactive e-modules. The training, conducted on August 8, 2024, involved 35 purposively selected elementary educators from the Metro City area. The program consisted of three phases: (1) foundational knowledge delivery on interactive e-modules, (2) hands-on training and mentoring on module development, and (3) evaluation of training effectiveness. Data were collected through questionnaires and participant observations, and analyzed using a qualitative approach. The findings revealed that participants significantly improved their theoretical understanding and practical skills related to interactive e-module design. Moreover, they demonstrated increased motivation and readiness to apply these digital tools in classroom settings, indicating the potential scalability of such training for broader educational contexts.